Comparing foreign intelligence : - edited by Roy Godson. (Pergamon-Brassey's International Defense Publishers, 1988)
Introduction / Roy Godson -- The study of intelligence in the United States / Kenneth G. Robertson -- Historical research on the British intelligence community / Christopher Andrew -- The study of the Soviet intelligence and security system / John J. Dziak -- Intelligence in an Arab Gulf state / Dale F. Eickelman -- Political intelligence in non-Western societies / Adda Bozeman.